Patient satisfaction with advanced practice physiotherapy internationally: A systematic mixed studies review - Chris Davis; Tim Noblet; Jodie Breach; Jai Mistry; Kaitlyn Maddigan; Katie Kowalski; Alison Rushton (PLoS ONE, 2026)
Introduction Advanced practice physiotherapy (APP) is internationally recognised as a higher level of practice involving expert clinical and analytical skills to manage complex patient needs. Patient satisfaction measures how pleased someone is with their care, comprises human and system attributes, and is an indicator of patient experience (quality). Patient satisfaction with APP appears high, but no comprehensive evidence synthesis across settings exists. Objectives were to evaluate patient satisfaction with APP internationally, and evaluate human and system attributes of patient satisfaction with APP. Materials and methods Systematic mixed studies review using a parallel-results convergent synthesis design. Key databases and grey literature were searched for studies measuring patient satisfaction with APP across clinical fields from inception to September 9 th , 2025. Screening, data-extraction, and quality appraisal were completed in parallel by two reviewers. Narrative (quantitative) and thematic (qualitative) syntheses were integrated through discussion, and GRADE/GRADE-CERQual assessed evidence confidence and certainty, Results 35 high (n=8), moderate (n=16), and low (n=11) quality studies were included. Narrative synthesis found very low certainty evidence for high overall and human attributes of patient satisfaction, and mostly high system attributes of patient satisfaction. Thematic synthesis found moderate-high confidence evidence of human attributes of patient satisfaction (proficient communication and interpersonal skills, credible and competent experts, patient empowerment and self-management, thorough assessments) and moderate confidence evidence of system attributes of patient satisfaction (fast access to specialist care, convenient location and amenities, integrated care). Conclusion Human and system attributes drive high patient satisfaction with APP. High-confidence evidence suggests that AP physiotherapists themselves are integral to patient satisfaction, as found across research in other professions. Quantitative evidence certainty is very-low, therefore future high-quality research is needed to guide APP service development.